Unmet supportive care needs and determinants among cancer patients treated at University of Gondar Specialized Hospital, Northwest Ethiopia: A prospective cross-sectional study - Gebresillassie, Begashaw Melaku; Ayele, Asnakew Achaw; Abegaz, Tadesse Melaku (Journal of oncology pharmacy practice, 2021)
Assessment of supportive care needs is an important requirement to plan supportive care intervention. This study aimed to assess the unmet supportive care needs of cancer patients treated at the University of Gondar Specialized Hospital, Ethiopia. A prospective cross-sectional study was conducted from January 1, 2017 to August 30, 2017. Adult (18 years and greater) cancer patients and those who were receiving therapy were included. The 34-Item short-form Supportive Care Needs Survey(SCNS-SF34) tool was used to assess unmet needs. The data collected were analyzed using SPSS version-21. A total of 150 interview guides were included in the analysis (97.4% of response rate). In the majority of 65(43.3%) the participants, the disease was metastasized even though they have undergone surgery 78 (52%). The overall mean score level of unmet need for cancer care was 3.49. The highest unmet need mean score was reported from the health system and information need domain. A significant unmet need difference concerning different need domain was found in sex, age, residence, occupation status, and monthly income. Sex and residence were found to be independent predicting factors for unmet supportive care needs. The overall level of unmet need was high. A significant unmet need difference was found in sex, age, residence, occupation status, and monthly income. Sex and residence were found to be independent predicting factors. Hence, professionals working in the oncology unit should be aware of unmet needs and expect changes over time. Certain programs and services to address the identified unmet needs should be urgently provided.